Students' Perspective: Virtual-Based Learning amid the Covid-19 Pandemic by Pre-Service Teachers in Rural Area, Thailand - Eliyana, Ema (Universitas Muhammadiyah Gresik, 2021)
By the end of 2019, Covid-19 outbreak has hit the whole world, and its impact has changed the learning process from face-to-face learning to virtual-based learning. This phenomenon also affected the learning process conducted by pre-service teachers in the internship program held by the University of Muhammadiyah Gresik in rural areas of Loei, Thailand. Due to the pandemic, the process was turned online. The online learning was a challenge for pre-service teachers because teaching online has never been done before, and the pre-service teachers didn't have much experience in it. The pre-service teachers felt that problems occurred were mostly due to limited signals and language differences that made it difficult for the pre-service teachers to communicate with the students. Therefore, to see a different view from the students, the researchers were interested to know the students' perspective towards virtual-based learning implemented by the pre-service teachers in a rural area of ​​Bankhoksrijaroen School. The researchers distributed a survey to 37 students to find out their perspective about virtual-based learning. The result showed that the students had several problems such as differences in language, internet connection, limited learning media, and less effective learning process. However, there was a difference between virtual-based learning and conventional learning, but it was not considered a problem regardless of the unknown ending of the pandemic. The virtual-based learning was deemed able to replace face-to-face learning process, and the students also stated that face-to-face learning was not necessary to be implemented during the pandemic.